AKAD MUDHARABAH PADA PRODUK TABUNGAN HAJI DI BSI KCP PANORAMA BENGKULU : FAKTOR PENDUKUNG & PENGHAMBAT - Ardian Pramesti Vita Mayang Sari; Romi Adetio Setiawan; Makmur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the mudharabah contract in the hajj savings product at Bank Syariah Indonesia (BSI) KCP Panorama Bengkulu and to identify the supporting factors, inhibiting factors, and customers’ perceptions regarding transparency and fairness in the mudharabah contract. This research employed a qualitative approach with a descriptive research design. Data collection techniques included in-depth interviews, observation, and documentation. The informants consisted of the Branch Operations & Service Manager (BOSM), Customer Service (CS), and five hajj savings customers. Data analysis was conducted using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The results indicate that the implementation of the mudharabah contract in the hajj savings product at BSI KCP Panorama Bengkulu has been carried out in accordance with Islamic economic principles. The contract applied is mudharabah muthlaqah, where customers act as shahibul maal and the bank acts as mudharib. The profit-sharing system is implemented based on a predetermined ratio agreed upon at the beginning of the contract. Supporting factors include the high public interest in performing the hajj pilgrimage, a flexible savings system, and effective bank services and promotions. Meanwhile, inhibiting factors include low public literacy regarding Islamic banking, the relatively small profit-sharing ratio, and customers’ economic conditions. Customers generally perceive the transparency and fairness of the mudharabah contract positively, although their understanding of the profit-sharing mechanism remains limited. This study recommends enhancing Islamic financial literacy and education to optimize the implementation of the mudharabah contract.